ANALISIS PENGARUH KEPEMIMPINAN, KOMPENSASI, PELATIHAN DAN PENGEMBANGAN TERHADAP KEPUASAN KERJA DAN PRODUKTIVITAS KERJA PEGAWAI BADAN PERTANAHAN NASIONAL SE- PROVINSI NUSA TENGGARA BARAT - cici irianti; Agusdin agusdin; hermanto hermanto (JMM UNRAM - MASTER OF MANAGEMENT JOURNAL, 2017)
This research is aimed at analyzing the effect of leadership on work satisfaction, the effect ofcompensation on work satisfaction, the effect of training and development on work satisfaction, theeffect of leadership of productivity, the effect of compensation on productivity, the effect of trainingand development on productivity, and the effect of work satisfaction on productivity of the ofemployees of national land agency of West Nusatenggara.This research is quantitative-associative causal study. The respondents are the civil servant ofland agency of West Nusatenggara who had been working for at least 5 years and have the positionof the head off sub-division (echelon IV) in provincial and district office in West Nusatenggara. Theyare 79 respondents from who the data collected through questionnaires. The data were analyzed withPartial Least Square (PLS) using software of SmartPLS version 3.The research showed that leadership has positive but not significant effect on work satisfaction,compensation has positive and significant effect on work satisfaction, training and development haspositive and significant effect on work satisfaction, leadership has positive but not significant effecton productivity, compensation has negative and not significant effect on productivity, training anddevelopment has positive but not significant effect on productivity, work satisfaction has positive andsignificant effect on productivity of employees of national land agency of West Nusatenggara.Compensation has dominant effect on work satisfaction, and work satisfaction also has dominanteffect of the productivity of employees of national land agency of West Nusatenggara.Keywords: leadership, work satisfaction, compensation, training and development, and productivity.